3D structure and immunogenicity of Plasmodium falciparum sporozoite induced associated protein peptides as components of fully-protective anti-malarial vaccine (2011)
SIAP-1 and SIAP-2 are proteins which are implicated in early events involving Plasmodium falciparum infection of the Anopheles mosquito vector and the human host. High affinity HeLa and HepG2 cell binding conserved peptides have been previously identified in these proteins, i.e. SIAP-1 34893 ( 421KVQGLSYLLRRKNGTKHPVY 440) and SIAP-1 34899 ( 541YVLNSKLLNSRSFDKFKWIQ 560) and SIAP-2 36879 ( 181LLLYSTNSEDNLDISFGELQ 200). When amino acid sequences have been properly modified (replacements shown in bold) they have induced high antibody titres against sporozoites in Aotus monkeys (assessed by IFA) and in the corresponding recombinant proteins (determined by ELISA and Western blot). 1H NMR studies of these conserved native and modified high activity binding peptides (HABPs) revealed that all had ?-helical structures in different locations and lengths. Conserved and corresponding modified HABPs displayed different lengths between the residues fitting into MHCII molecule pockets 1-9 and different amino acid orientation based on their different HLA-DR?1 * binding motifs and binding registers, suggesting that such modifications were associated with making them immunogenic. The results suggested that these modified HAPBs could be potential targets for inclusion as components of a fully-effective, minimal sub-unit based, multi-epitope, and multistage anti-malarial vaccine. © 2011 Elsevier Inc..